Cyber-physical architecture assisted by programmable networking - Jose Rubio-Hernan; Rishikesh Sahay; Luca De Cicco; Joaquin Garcia-Alfaro (Internet Technology Letters, 2018)
Cyber-physical technologies are prone to attacks in addition to faults and failures. The issue of protecting cyber-physical systems should be tackled by jointly addressing security at both cyber and physical domains in order to promptly detect and mitigate cyber-physical threats. Toward this end, this letter proposes a new architecture combining control-theoretic solutions together with programmable networking techniques to jointly handle crucial threats to cyber-physical systems. The architecture paves the way for new interesting techniques research directions and challenges which we discuss in our work
Keywords: control theory; cyber-physical systems; programmable networking; software-defined networks; supervisory control and data acquisition